Potential indicators of neighbourhood solar access in urban planning - Solar access metrics simulated for urban design iterations and case studies - Czachura, Agnieszka (Lund University, 2022)
The data contains results of a study that analysed solar access metrics for urban planning purposes. The purpose was to evaluate metric correlations to find suitable simple indicators of solar performance that can be applied to assess urban designs.

The data contains inputs for creating the neighbourhood design iterations and metrics as outputs of simulations. Neighbourhood models were created using Rhino 7 and Grasshopper, while metrics were simulated using Grasshopper and Ladybug Tools.

The metrics are described in the review article: Czachura, A., Kanters, J., Gentile, N., & Wall, M. (2022). Solar Performance Metrics in Urban Planning : A Review and Taxonomy. In Buildings (No. 393; Vol. 12, Issue 4). https://doi.org/10.3390/buildings12040393

The model setup is described in the article: Czachura, Agnieszka, Niko Gentile, Jouri Kanters, and Maria Wall. 2022. "Identifying Potential Indicators of Neighbourhood Solar Access in Urban Planning" Buildings 12, no. 10: 1575. https://doi.org/10.3390/buildings12101575

The excel file comprises of five data sheets: two containing data descriptions and three containing research data. The results are solar access metrics, which were used in a correlation study and other statistical analyses to determine their suitability for urban planning assessment purposes.

Sheet 1 'metric_descriptions': Description of metrics

Sheet 2 'headings': Description of headings

Sheet 3 'Iterations_Stockholm': Neighbourhood models generated in an iterative process using geometrical constraints were simulated to obtain multiple solar access metrics, assuming the Stockholm climate.

Sheet 4 'Iterations_Frankfurt': The same neighbourhood models generated in an iterative process using geometrical constraints were simulated to obtain multiple solar access metrics, assuming the Frankfurt climate.

Sheet 5 'Case-Studies_Frankfurt': Case studies of real neighbourhood designs from Malmö city were simulated to obtain multiple solar access metrics, assuming the Frankfurt climate. These metric datasets were used for validation purposes.

Data available in xlsx and csv format

Datan innehåller resultat från en studie som analyserade mätvärden som visar solenergitillgångsmått för stadsplaneringsändamål. Syftet var att utvärdera korrelationer mellan värdeindikatorer för att hitta lämpliga enkla indikatorer på solprestanda som kan användas för att bedöma stadsdesign.

Datan innehåller indata för att skapa designiterationer av kvarter och mätvärden som utdata från simuleringar. Kvartersmodeller skapades med Rhino 7 och Grasshopper, medan mätvärden simulerades med Grasshopper och Ladybug Tools.

Mätvärden beskrivs i review-artikeln: Czachura, A., Kanters, J., Gentile, N., & Wall, M. (2022). Solar Performance Metrics in Urban Planning : A Review and Taxonomy. In Buildings (No. 393; Vol. 12, Issue 4). https://doi.org/10.3390/buildings12040393

Modellen beskrivs i artikeln: Czachura, Agnieszka, Niko Gentile, Jouri Kanters, and Maria Wall. 2022. "Identifying Potential Indicators of Neighbourhood Solar Access in Urban Planning" Buildings 12, no. 10: 1575. https://doi.org/10.3390/buildings12101575

Excelfilen består av fem datablad: två som innehåller databeskrivning och tre som innehåller forskningsdata. Resultaten är mätvärden för soltillgång, som användes i en korrelationsstudie och andra statistiska analyser för att bestämma deras lämplighet för bedömning av stadsplanering.

Blad 1 'metric_descriptions': Beskrivning av mätvärden

Blad 2 'headings': Beskrivning av rubriker

Blad 3 'Iterations_Stockholm': Grannskapsmodeller som genererats i en iterativ process med geometriska begränsningar simulerades för att erhålla flera mätvärden för soltillgång, under antagande av Stockholmsklimatet.

Blad 4 'Iterations_Frankfurt': Samma grannskapsmodeller som genererades i en iterativ process med geometriska begränsningar simulerades för att erhålla flera mätvärden för soltillgång, under antagande av Frankfurts klimat.

Blad 5 'Fallstudier_Frankfurt': Fallstudier av verkliga stadsdelar från Malmö stad simulerades för att erhålla flera mätvärden för soltillgång, under antagande av Frankfurts klimat. Dessa metriska datauppsättningar användes för valideringsändamål.

Data finns tillgängliga i xlsx och csv-format.
Potentiella indikatorer på tillgång till solenergi i stadsplanering - Mätvärden för soltillgång simulerade för stadsdesigniterationer och fallstudier
Keywords: environmental indicators; miljöindikatorer; statistical models; statistiska modeller; urban design; stadsplanering; sunlight; urban planning; solar access; tillgång till solenergi; daylight; dagsljus; Architectural Engineering; Arkitekturteknik; Other Civil Engineering; Annan samhällsbyggnadsteknik; Energy Engineering; Energiteknik